Characteristics of the periodontal status in pregnant women of the San Pablo Mother and Child Hospital in Asunción, Paraguay - Méndez Báez, María Gisselle (2018)
Objective: To determine characteristics of the periodontal status in pregnant women attending the San Pablo Mother and Child Hospital in Asunción, Paraguay, during December of 2015 to February of 2016. Methods: A descriptive cross-sectional observational study was conducted on pregnant patients who attended their first prenatal visit. A survey on sociodemographic factors, oral hygiene habits and oral health instructions, was conducted by health personnel. The periodontal status’ assessment was stated as part of a clinical data record sheet, which included the Gingival Index (GI) of Löe and Silness of the lower anterior sextant. Results: A total of 96 patients between 15 and 37 years old, were evaluated, with an average of 23.8, standard deviation 5.47. Results stated that gingivitis predominated in pregnant women in 85.4% (n=82). Moderate gingivitis prevailed (49%), both in the first and third trimesters, while severe gingivitis had less prevalence (3.1%). Conclusions: Gingivitis predominated in pregnant women in 85.4%. Moderate gingivitis being prevalent in 49% according with the Löe and Silness GI results.